2017
DOI: 10.1080/17470218.2016.1182193
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the generalizability of context-driven control

Abstract: Context-driven control refers to the fast and flexible weighting of stimulus dimensions that may be applied at the onset of a stimulus. Evidence for context-driven control comes from interference tasks in which participants encounter a high proportion of incongruent trials at one location and a high proportion of congruent trials at another location. Since the size of the congruency effect varies as a function of location, this suggests that stimulus dimensions are weighted differently based on the context in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(92 citation statements)
references
References 33 publications
12
78
2
Order By: Relevance
“…This finding, of course, cannot be explained by (context-specific) contingency learning and is therefore seemingly inconsistent with the results of Schmidt and Lemercier (2018). A subsequent series of experiments did, however, fail to replicate this key transfer effect (Hutcheon & Spieler, 2017), though the original authors were able to replicate the effect again (Crump, Brosowsky, & Milliken, 2017), albeit with much smaller effect sizes. Although further replications from independent labs would be desirable, these results do suggest that some small CSPC effect might still remain after controlling for (Bcontext-specific^) contingency biases.…”
Section: Context-specific Proportion Congruent (Cspc) Effectsmentioning
confidence: 88%
“…This finding, of course, cannot be explained by (context-specific) contingency learning and is therefore seemingly inconsistent with the results of Schmidt and Lemercier (2018). A subsequent series of experiments did, however, fail to replicate this key transfer effect (Hutcheon & Spieler, 2017), though the original authors were able to replicate the effect again (Crump, Brosowsky, & Milliken, 2017), albeit with much smaller effect sizes. Although further replications from independent labs would be desirable, these results do suggest that some small CSPC effect might still remain after controlling for (Bcontext-specific^) contingency biases.…”
Section: Context-specific Proportion Congruent (Cspc) Effectsmentioning
confidence: 88%
“…1b, c). This suggests that a spatial location can come to serve as a bottom-up predictive cue for retrieving a context-appropriate top-down control set (for additional discussion, see Crump et al, 2017;Hutcheon and Spieler, 2017). Other recent studies have demonstrated this type of modulation of the congruency effect using a wide variety of different contextual cues, including stimulus location Corballis & Gratton, 2003;Crump, 2016;Crump et al, 2017;Crump, Gong, & Milliken, 2006;Hübner & Mishra, 2016;King, Korb, & Egner, 2012;Weidler & Bugg, 2016), font (Bugg, Jacoby, & Toth, 2008;Crump, 2016), shape (Crump, Vaquero, & Milliken, 2008), color (Vietze & Wendt, 2009), social categories (Cañadas, Rodríguez-Bailón, Milliken, & Lupiáñez, 2013) and incidental sematic cues (Blais, Harris, Sinanian, & Bunge, 2015).…”
Section: Behavioral Evidence For Context-control Learningmentioning
confidence: 91%
“…Although many successful replications and variations of the CSPC exist, there are indications that it underlies strict limitations. Hutcheon and Spieler (2017) have tried to replicate the original findings of Crump and Milliken (2009) who first added unbiased items to their design to rule out any lower level processes in responding as source of the effect. Their results from three experiments did not match the original results: They did not find any CSPC effects either in the frequency biased or in the unbiased transfer items.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of our and earlier results (cf. Crump et al, 2017; Hutcheon & Spieler, 2017), some methodological recommendations that can minimise a large part of this noise can be inferred. A different type of transfer manipulation, for example, can solve the issue of attenuated context cues.…”
Section: Discussionmentioning
confidence: 99%